Telbivudine Treatment during Late Pregnancy Prevents Mother-to-Child Transmission of Hepatitis B Virus: A Retrospective Study - Mengzhi Cai; Yanli Hao; Jianxin Zhong; Wei Yao; Xia Cao; Guifang Gu; Gang Qin (Canadian Journal of Gastroenterology and Hepatology)
Purpose. To investigate the efficacy of telbivudine (LdT) in blocking mother-to-child transmission (MTCT) of hepatitis B virus (HBV) during late pregnancy. Methods. A total of 651 pregnant women aged 18-40 in Nantong Third People’s Hospital and Hospital affiliated to Nantong University with positive hepatitis B surface antigen (HBsAg) and HBV DNA were enrolled between January 2011 and December 2015. Patients with HBV DNA≥106 copies/mL (n=251) received LdT during late pregnancy according to the patients’ will, while 136 high viral patients with HBV DNA≥106 copies/mL who did not take LdT therapy and 268 low viral patients with HBV DNA<106 copies/mL served as the controls. Results. At 7 months and 1 year postpartum, the basal HBV DNA serum level of treated patients declined significantly (P<0.001), while no obvious decline was observed in the untreated high viraemic controls (P<0.05) and untreated low viraemic controls (P<0.05). Only 1 infant (0.4%) in LdT group was HBsAg positive at 7 months, while 14 (5.2%) were in the untreated low viraemic controls (P<0.001) and 15 (11.0%) were in untreated high viraemic controls (P<0.001). Conclusion. For pregnant women with HBV DNA≥106 copies/mL, the use of LdT during late pregnancy could effectively reduce the MTCT rate of HBV.